MERANCANG MANAJEMEN AGRIBISNIS SYARIAH DI DESA BOJONG JENGKOL, KECAMATAN CIAMPEA, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Elisa Rahman (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Bojongjengkol Village, Ciampea District, Bogor Regency, to be precise, in Ckirai Village, is the place where community service activities are carried out. This community service implementation will be carried out for 30 days or 1 full month starting from August 25 to September 23 2021. The method of implementing this community service activity is carried out through open discussions and questions and answers with farmer groups in Bojong Jengkol Village, District Ciampea. During the discussion, issues regarding the community of the Cikirai Village farmer group emerged. Some of the problems were discussed by discussion and counseling - counseling. However, a bigger problem requires government policy, such as the price of organic fertilizer. The aim of this community service is so that the community can increase their income and productivity of agricultural processing products. Sharia agribusiness management planning includes marketing planning, production planning, financial planning, and human resource planning.